2022
DOI: 10.4143/crt.2021.764
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Immune Checkpoint Inhibitors in Non–Small Cell Lung Cancer Patients with Liver Metastases: A Network Meta-Analysis of Nine Randomized Controlled Trials

Abstract: This network meta-analysis (NMA) was conducted to compare the efficacy of immune checkpoint inhibitors (ICIs) in advanced non-small cell lung cancer (NSCLC) patients with liver metastases. Materials and MethodsEnglish literature was retrieved from the PubMed, American Society of Clinical Oncology (ASCO), and European Society for Medical Oncology (ESMO) databases from January 2015 to January 2021. We pooled the overall survival (OS) and progression-free survival (PFS) hazard ratios (HRs) using a network meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…Until now, there has been insufficient evidence to determine which PD-1 or PD-L1 inhibitors are more appropriate for lung cancer patients with liver metastases. In a recent network meta-analysis of nine RCTs ( 56 ), pembrolizumab plus chemotherapy and atezolizumab plus bevacizumab plus chemotherapy provided the most benefit in the treatment of NSCLC patients with liver metastases, in terms of both OS and PFS. Based on these results, large head-to-head trials should be conducted to find the optimal regimen for this type of patient.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there has been insufficient evidence to determine which PD-1 or PD-L1 inhibitors are more appropriate for lung cancer patients with liver metastases. In a recent network meta-analysis of nine RCTs ( 56 ), pembrolizumab plus chemotherapy and atezolizumab plus bevacizumab plus chemotherapy provided the most benefit in the treatment of NSCLC patients with liver metastases, in terms of both OS and PFS. Based on these results, large head-to-head trials should be conducted to find the optimal regimen for this type of patient.…”
Section: Discussionmentioning
confidence: 99%
“…In another meta-analysis, the authors compared the efficacy of different immunotherapy agents in advanced NSCLC patients with liver metastasis, and found that the efficacy of ICIs depends on the combination strategy. 40 Pembrolizumab plus chemotherapy, and atezolizumab plus bevacizumab plus chemotherapy were superior to other regimens for liver metastasis patients. 40 These are consistent with our findings, again suggesting that treatment combination options are one of the factors affecting the efficacy of immunotherapy.…”
Section: Discussionmentioning
confidence: 94%
“… 40 Pembrolizumab plus chemotherapy, and atezolizumab plus bevacizumab plus chemotherapy were superior to other regimens for liver metastasis patients. 40 These are consistent with our findings, again suggesting that treatment combination options are one of the factors affecting the efficacy of immunotherapy. Additional studies 41 , 42 also assessed the relationship between liver metastasis and efficacy of immunotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…[86] Moreover, a network meta-analysis of 1141 patients with NSCLC and LMs showed that atezolizumab combined with bevacizumab plus chemotherapy, and pembrolizumab combined with chemotherapy resulted in superior PFS compared with other immunotherapy, chemotherapy, or anti-angiogenic treatments. [87] In the KEYNOTE-189 study (NCT02578680), patients with advanced nonsquamous NSCLC and LMs received combined chemoimmunotherapy (n = 66, active arm) or standard chemotherapy (n = 49, control arm). [88] Firstline pembrolizumab combined with pemetrexed exhibited a signi cant increase in PFS (9.0 months vs. 4.9 months, HR: 0.48, 95% CI: 0.40-0.58) and OS (22.0 months vs. 10.7 months, HR: 0.56, 95% CI: 0.45-0.70) in metastatic nonsquamous NSCLC, regardless of the LM status, with manageable safety and tolerability.…”
Section: Immunotherapy In Combination With Chemotherapymentioning
confidence: 99%
“…[ 86 ] Moreover, a network meta-analysis of 1141 patients with NSCLC and LMs showed that atezolizumab combined with bevacizumab plus chemotherapy, and pembrolizumab combined with chemotherapy resulted in superior PFS compared with other immunotherapy, chemotherapy, or anti-angiogenic treatments. [ 87 ]…”
Section: Prospective Preclinical and Clinical Strategies For Targetin...mentioning
confidence: 99%